(untitled) (The Review of Diabetic Studies, 2024)
The healthcare industry is realizing that there is an intrinsic connection between the performance of nurses and the administrative support systems, as well as the measures taken to provide workplace security. In this study, the complex role of the hospital administration, the support mechanisms related to the psychosocial well-being of nurses, the provision of the necessary infrastructural support related to health security, and the performance of the nurses is explored in depth. From the various cross-section data related to different hospital environments, the findings of this study are that there is an enormous positive role of the hospital administration, along with the support systems related to the psychosocial well-being of the nurses, towards the overall performance of the nurses, and that workplace health security measures can lead to an overall positive shift in the job-related efficiency and performance of the nurses, which is an intrinsic part of the concept of health security today.